Cyanobacteria from coastal lagoons of Southern Brazil: coccoid organisms - Martins, Mariéllen Dornelles [UNESP]; Branco, Luis Henrique Zanini [UNESP]; Werner, Vera Regina (Sociedade Botânica de São Paulo, 2012)
Considering the great ecological importance of the cyanobacteria and the need for more detailed information about these organisms in Brazilian waters, this paper provides taxonomic information about the unicellular cyanobacteria flora in lagoon systems along the coastal plains of Rio Grande do Sul State. Sampling was performed in different freshwater bodies along the eastern (Casamento Lake area) and western (near the city of Tapes) banks of the Patos Lagoon (30º40' S-30º10' S and 50º30' W-51º30' W). The samples were collected once in the rainy season and once in the dry season (from May 2003 to December 2003) using a plankton net (25 µm mesh) in pelagic and littoral zones, and by squeezing the submerged parts of aquatic macrophytes. Thirty one species belonging to the families Synechoccocaceae (7 taxa), Merismopediaceae (12 taxa), Chamaesiphonaceae (1 taxon), Microcystaceae (4) and Chroococcaceae (7 taxa) were identified. Among these species, five are reported for the first time in Rio Grande do Sul State: Chamaesiphon amethystinus (Rostafinski) Lemmermann, Chroococcus minimus (Keissler) Lemmermann, Coelomoron pusillum (Van Goor) Komárek, Coelosphaerium kuetzingeanum Naegeli, and Cyanodictyon tubiforme Cronberg.
Keywords: Casamento lake; Chroococcales; Patos Lagoon; Synechococcales